(3JcQje GdEfSGf HGdYbd hGdYde hGdMVGQI (B/s - (3Ndjd, YHO GdQDha MSf,s 1937-2008 ((3LOI, GdSYhOjI (B:s (3eOjfI GdWjHGJ GdYGdejI ddYdhe hGdeYQaI,s, 2000)
(3jJfGhd cJGH (B"(3JcQje GdEfSGf HGdYbd hGdYde hGdMVGQI(B" (3hGdPj bGe HJCdjag YHO GdQDha MSf Ndjd aj (B(936) (3UaMI ef GdbWY GdeJhSW hGdPj UOQ Vef SdSdI (B"(3ehShYI GdWjHGJ ddYdhe hGdeYQaI(B" (3ehba GdESdGe ef GdEfSGf, hcja cQe Gddg gPG GdEfSGf ef NdGd JejjRg HGdYbd hMKg Ydi GdYde hEYeGQ GdCQV dEfTGA MVGQI ESdGejI bGFeI Ydi GdYde hGdJOHQ aj EWGQ JYGdje GdOjf GdSeMI(B.s
(3HHdjhLQGajI (B: (3UaMI (B905-919.s
Keywords: (3GdESdGe hMbhb GdEfSGfs; (3GdMVGQI GdESdGejIs